NIK signaling axis regulates dendritic cell function in intestinal immunity and homeostasis. (November 2018) - Jie, Zuliang; Yang, Jin-Young; Gu, Meidi; Wang, Hui; Xie, Xiaoping; Li, Yanchuan; Liu, Ting; Zhu, Lele; Shi, Jianhong; Zhang, Lingyun; Zhou, Xiaofei; Joo, Donghyun; et al.
Abstract Dendritic cells (DCs) play an integral role in regulating mucosal immunity and homeostasis, but the signaling network mediating this function of DCs is poorly defined. We identified the noncanonical NF-κB-inducing kinase (NIK) as a crucial mediator of mucosal DC function. DC-specific NIK deletion impaired intestinal immunoglobulin A (IgA) secretion and microbiota homeostasis, rendering mice sensitive to an intestinal pathogen, Citrobacter rodentium. DC-specific NIK was required for expression of the IgA transporter polymeric immunoglobulin receptor (pIgR) in intestinal epithelial cells, which in turn relied on the cytokine IL-17 produced by TH 17 cells and innate lymphoid cells (ILCs). NIK-activated noncanonical NF-κB induced expression of IL-23 in DCs, contributing to the maintenance of TH 17 cells and type 3 ILCs. Consistent with the dual functions of IL-23 and IL-17 in mucosal immunity and inflammation, NIK deficiency also ameliorated colitis induction. Thus, our data suggest a pivotal role for the NIK signaling axis in regulating DC functions in intestinal immunity and homeostasis. The kinase NIK activates a noncanonical NF-κB2 signaling pathway. Shao-Cong Sun and colleagues show that conditional loss of NIK in dendritic cells alters gut microbiome composition and TH 17 cell responses, as a result of reduced expression of IL-23, pIgR and fecal IgA transcytosis.